Evaluation of Larvicidal Efficacy of Ricinus communis (Castor) Plant Extract and Synthesized Green Silver Nanoparticles against Aedes albopictus - Muhammad Waris; Shabab Nasir; Azhar Rasule; Iqra Yousaf (Tehran University of Medical Sciences, 2020)
Background: Aedes mosquitoes are the most important group of vectors having ability of transmitting pathogens including arboviruses that can cause serious diseases like Chikungunya fever, Dengue fever and Zika virus in human. Biosynthesis and the use of green silver nanoparticles (AgNPs) is an important step in the search of reliable and ecofriendly control of these vectors. Methods: In this study an aqueous leaves extract of Ricinus communis (castor) and silver nanoparticles (AgNPs) synthesized from this extract were evaluated as larvicidal agent for 2nd and 3rd instar larvae of the Aedes albopictus. Different concentrations (50, 100, 150, 200 and 250ppm) of plant extract and synthesized nanoparticles were prepared and applied on second and third instar larvae. The percent mortality was noted after 6, 12, 18, 24, 30, 36, 42 and 48H of exposure and subjected to probit analysis to calculate LC50 and LC90. Results: Synthesized Ag+ nanoparticles were characterized by UV-Vis spectroscopy, Fourier transform infrared spectroscopy (FT-IR), and energy-dispersive X-ray spectroscopy (XRD). The nanoparticles were more toxic against larvae of Ae. albopictus with LC50 value (49.43ppm) and LC90 value (93.65ppm) for 2nd instar larvae and LC50 (84.98ppm) and LC90 (163.89ppm) for 3rd instar larvae as compared to the plant extract (149.58ppm, 268.93ppm) and (155.58ppm, 279.93ppm) for 2nd and 3rd instar larvae of Ae. albopictus respectively after 48H. Conclusion: Our results suggest the extract of R. communis and synthesized nanoparticles as excellent replacement of chemical pesticides to control the vector mosquitoes.